1996
DOI: 10.1002/(sici)1098-2396(199610)24:2<135::aid-syn5>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

MK-801 increases locomotor activity without elevating extracellular dopamine levels in the nucleus accumbens

Abstract: In vivo microdialysis was used in freely moving rats to determine whether the locomotor stimulant effects of dizocilpine maleate (MK-801) were related to increased dopamine (DA) release within the nucleus accumbens (N. Acc.). Each experiment began with a baseline period of at least 2 h (starting 15-20 h after insertion of concentric, removable dialysis probes), during with activity records and dialysate samples were collected every 20 min. Rats in the first experiment then were injected with MK-801 (0.125, 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
19
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 66 publications
6
19
1
Order By: Relevance
“…However, in the present study subchronic PCP treatment substantially increased amphetamine-induced locomotor hyperactivity without altering the NAc dopamine levels, suggesting that the enhancement of activity could not be attributed to increased activity within the mesoaccumbens system. This finding is consistent with the results of both Druhan et al (1996) and Wolf et al (1994), who observed that MK-801 potentiated amphetamine-induced hyperactivity without, itself, inducing dopamine release in NAc or potentiating amphetamine-induced dopamine release. It has recently been suggested that locomotor effects of acutely administered PCP reflect its actions within PFC rather than NAc (Adams and Moghaddam, 1998;Jentsch et al, 1998b) which is consistent with an earlier work of Nabeshima et al (1983).…”
Section: Dissociation Between Behavioral Effects and Nac Dopamine Relsupporting
confidence: 92%
“…However, in the present study subchronic PCP treatment substantially increased amphetamine-induced locomotor hyperactivity without altering the NAc dopamine levels, suggesting that the enhancement of activity could not be attributed to increased activity within the mesoaccumbens system. This finding is consistent with the results of both Druhan et al (1996) and Wolf et al (1994), who observed that MK-801 potentiated amphetamine-induced hyperactivity without, itself, inducing dopamine release in NAc or potentiating amphetamine-induced dopamine release. It has recently been suggested that locomotor effects of acutely administered PCP reflect its actions within PFC rather than NAc (Adams and Moghaddam, 1998;Jentsch et al, 1998b) which is consistent with an earlier work of Nabeshima et al (1983).…”
Section: Dissociation Between Behavioral Effects and Nac Dopamine Relsupporting
confidence: 92%
“…1B). These data confirm the notion that the hyperactivity induced by pharmacological or genetic suppression of NMDA receptor function is not related to the modulation of striatal extracellular dopamine levels (10)(11)(12)(30)(31)(32)(33).…”
Section: Striatal Extracellular Levels Of Dopamine Are Not Affected Bcontrasting
confidence: 63%
“…NMDA antagonists are reported to enhance amphetamine-induced locomotor activity following both acute (Sripada et al 1998;Druhan et al 1996; Turgeon and Roche 1999) and continuous (Jentsch et al 1998) treatment, although contrary results have also been obtained (Gandolfi et al 1992). For the present study, therefore, amphetamine-induced locomotor activity was monitored along with striatal dopamine release.…”
mentioning
confidence: 89%